The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1980
DOI: 10.1002/bjs.1800670218
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent torsion of the testis following previous surgical fixation

Abstract: Two cases of recurrent torsion of the testis following previous surgical fixation are described. The significance of this rare occurrence is discussed and it is recommended that total excision of the parietal tunica vaginalis is used for surgical fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 11 publications
(2 reference statements)
0
27
0
Order By: Relevance
“…Various methods of fixation are used by surgeons. There have been many reports of torsion occurring after previous testicular fixation (May and Thomas, 1980;Vorstman and Rothwell, 1982;Thurston and Whitaker, 1983). It has been suggested that the use of a non-absorbable rather than an absorbable suture will prevent this complication (Tawil and Gregory, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Various methods of fixation are used by surgeons. There have been many reports of torsion occurring after previous testicular fixation (May and Thomas, 1980;Vorstman and Rothwell, 1982;Thurston and Whitaker, 1983). It has been suggested that the use of a non-absorbable rather than an absorbable suture will prevent this complication (Tawil and Gregory, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In the lower part of the testis, the descend ing branch of the testicular artery is sometimes present [13,14], Injuries to these main blood vessels can be avoided by shallow suturing of the tunica albuginea. Suture was done with silk, because recurrence of torsion has been reported after fixation using catgut [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The findings at the secondary operation conclusively proved that these techniques were insufficient and thus unreliable: a) in 20 cases the testes were found to be lying freely in the vaginal cavity without any remnants of the previous fixation; (3,6,10,14,15,17,18,21,23,25,32,34,35); b) in 6 cases testes were equally free, with very scant signs of the previous operation (1,12,15,26,30,31); c) in one case the testis revolved around a previous suture (20); and d) in 9 cases testes were anchored by a stretched-out adhesion which, acting like an axis, had tended to favor torsion instead of preventing it (7,12,20,29,32).…”
Section: Findings At Reoperationsmentioning
confidence: 97%
“…The results after the secondary operation were: four orchiectomies (11, 30 ± 32); a ªgangrenousº (sic) testis, which was left in place because the controlateral organ had been removed at the primary operation (26); five confirmed atrophies (14,15,17,33); three foreseeable atrophies, according to the surgeons own assessment (29,34); and 12 ªnormalº testes. Within this so-called ªnormalº group, in a substantial number of cases the findings described at the secondary operation cast serious doubts as to the final destiny of the testes involved.…”
Section: Sequelae Of Failuresmentioning
confidence: 99%